Determinan Kejadian Wasting pada Balita - Aurellia, Nur Aisya; Ramadhani, Anindita Ayu; Pamungkas, Khrisna Aji; Kartiasih, Fitri (Seminar Nasional Official Statistics, 2023)
Wasting is a serious problem because it has a significant impact on various sectors of life, especially hindering the progress of individuals and human resources in a country. The highest waste incident in Indonesia is in the Province of East Nusa Tenggara. Therefore, this study aims to analyze the factors that influence the incidence of under-five wasting in NTT Province in 2021. The research method used is multiple linear regression. The research findings show that the percentage of extremely poor people, the percentage of women who give birth to babies with low birth weight, and the percentage of two-year-old babies who have ever been breastfed have a significant effect on the percentage of toddlers wasting. As a solution, it requires a collaborative effort from governments, health agencies, civil society organizations, and the community as a whole to tackle the problem of wasting and improve the health and well-being of children.